Assistive Robot Model to Care for Patients with Covid-19 - Jesús D. OCAÑA; Erick G. FLORES; Víctor A. ANCAJIMA; Alex PACHECO (Communications of International Proceedings, 2020)
This research project consists of the design of a robot model, equipped with artificial intelligence, with the ability to deliver drugs to patients with COVID-19 during their hospitalization; in this way, health personnel are not exposed to the risk of contagion of this disease. The humanoid-looking assistance robot is programmed in such a way that the assistance personnel indicate by means of the numerical keyboard to which bed to go, the robot moves and locates the number of the patient's bed through pattern recognition, facilitating the medication and conclude with care. The sensor system detects the objects around it, capturing this information to transmit it to the neural networks, which tells the robot which way to move. Neural networks and computer vision are recorded on an Arduino microcontroller. The mathematical models were processed in the Matlab software and the results obtained from the simulations showed the operation of the robot with the learning response time of the neural networks, for the displacement and recognition of the patient's bed number. All these systematized actions are developed with the concurrent design methodology that contains five stages, conceptual design, kinematic analysis, dynamic analysis, mechanical design and simulation. The assistance robot was designed, with neural networks and artificial vision, adding sensors, actuators and peripherals.
Keywords: Assistive robot; artificial neural networks; artificial vision.